HIGHER EDUCATION OUTREACH: EXAMINING KEY CHALLENGES FOR ACADEMICS. Issue 4 (2nd October 2019) - Johnson, Matthew; Danvers, Emily; Hinton-Smith, Tamsin; Atkinson, Kate; Bowden, Gareth; Foster, John; Garner, Kristina; Garrud, Paul; Greaves, Sarah; Harris, Patricia; Hejmadi, Momna; Hill, David; et al.
ABSTRACT: How should academic staff engage in outreach with communities outside of the university? The need of academics to answer this question has intensified in the UK given the changing priorities of academic job roles, shaped by increasing institutional concern for widening participation, graduate employability and research impact in an era of austerity and high tuition fees. While university outreach professionals, such as those in widening participation, have access to a range of networks, resources and support mechanisms for outreach activity, academics often face a series of profession-specific pressures that make engagement in outreach complex and contingent. This article draws upon the experience of 25 academics from 18 different subject areas and 18 institutions to examine and provide responses to key challenges faced by academics involved in outreach in the UK. We examine such issues as: the conceptualisation of outreach; funding; recognition and management of workload; nurturing relationships with internal and external partners; capacity-building; commercial interests, payment and responsibility; pedagogical style and content; integration of outreach into curricula, and evaluation of programmes. The examination offered is not all encompassing, but acts as a series of reference points to consider the challenges faced by UK academics in an evolving outreach sector.